2002
DOI: 10.1023/a:1014856713942
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in Evaluation of Response to Neoadjuvant Breast Cancer Treatment Benefits of MRI

Abstract: MRI appears to be a valuable technique for assessment of response to chemotherapy and identification of multifocal disease prior to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
0
11

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(98 citation statements)
references
References 29 publications
3
83
0
11
Order By: Relevance
“…Several studies have suggested that MRI is a more accurate method of delineating residual tumour following neoadjuvant chemotherapy than clinical, ultrasound or mammographic assessment (Boetes et al, 1995;Abraham et al, 1996;Drew et al, 1999Drew et al, , 2001Fischer et al, 1999;Balu-Maestro et al, 2002;Rieber et al, 2002;Cheung et al, 2003;Rosen et al, 2003;Martincich et al, 2004;Warren et al, 2004). Chemotherapy-induced fibrosis has been shown to impair the evaluation of tumour by conventional radiological methods and physical examination (Cocconi et al, 1984;Segel et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that MRI is a more accurate method of delineating residual tumour following neoadjuvant chemotherapy than clinical, ultrasound or mammographic assessment (Boetes et al, 1995;Abraham et al, 1996;Drew et al, 1999Drew et al, , 2001Fischer et al, 1999;Balu-Maestro et al, 2002;Rieber et al, 2002;Cheung et al, 2003;Rosen et al, 2003;Martincich et al, 2004;Warren et al, 2004). Chemotherapy-induced fibrosis has been shown to impair the evaluation of tumour by conventional radiological methods and physical examination (Cocconi et al, 1984;Segel et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Magnetic resonance imaging (MRI) was reported to have results correlated better with pathology findings than mammography and obtained promising results when dynamic contrast agents are applied. [6][7][8] However, MRI is expensive and exogenous agents are needed for better contrast. In 1990s, diffuse optical tomography (DOT) has emerged with promises as an imaging tool for breast cancer screening and diagnosis because of its unique features such as non-ionizing radiation, low cost, and high intrinsic absorption contrast.…”
Section: Introductionmentioning
confidence: 99%
“…23 With a sensitivity ranging from 63% to 100%, the MRI scan seems to be an accurate method of delineating residual tumor volume after neoadjuvant therapy for large breast tumors. [25][26][27][28][29] In our study, clinicopathologic sizes were well correlated with breast imaging, which was performed to rule out breast-preserving surgery. However, postchemotherapy mammograms could show extensive calcifications or stable disease whereas histopathologic results revealed breast-conserving surgery feasibility.…”
Section: Discussionmentioning
confidence: 76%